Governing by virtue: Lord Burghley and the management of Elizabethan England - Jones, Norman Leslie (Oxford University Press, 2015)
Managing Elizabethan England -- Managing virtuously -- William Cecil, Lord Burthley, manager -- Managing locallly -- Managing through perception -- Managing up and managing down -- Managing money -- Managing war -- Managing the Protestan state -- Managing within the possible